Clinical Significance of Intermediate-Density Lipoprotein Cholesterol Determination as a Predictor for Coronary Heart Disease Risk in Middle-Aged Men - Yoshida, Hiroshi; Ito, Kumie; Manita, Daisuke; Sato, Ryo; Hiraishi, Chika; Matsui, Sadako; Hirowatari, Yuji (Frontiers in Cardiovascular Medicine, 2021)
Background: Not only LDL cholesterol but also non-HDL cholesterol (non-HDL-C), VLDL cholesterol (VLDL-C) and IDL cholesterol (IDL-C) have been reported to be a significant risk marker for coronary heart disease (CHD). We reported the relevance of IDL-C to Framingham risk score (F-score), but the present study addressed the relevance of IDL-C to Suita score (S-score), a risk score for coronary heart disease (CHD) development for Japanese individuals in addition to F-score. Methods: Cholesterol levels of lipoproteins, including triglyceride (TG)-rich lipoproteins (IDL and VLDL), were measured by an anion exchange high-performance liquid chromatography. This study enrolled 476 men, aged mean 51 years and free of CHD and stroke. Results: Non-HDL-C, IDL-C and VLDL-C significantly correlated with F-score and S-score. In the multiple stepwise regression analysis, IDL-C as well as body mass index (BMI) significantly correlated with both F-score and S-score in both the total subjects and the subjects without drug therapy. The multivariate logistic analysis with the model composed of BMI and IDL-C as predictor variables demonstrated that 1SD increase in IDL-C was an independent predictor for 10-year CHD risk> 10% of F-score (OR 1.534, 95%CI 1.266-1.859, p< 0001) and that of S-score (OR 1.372, 95%CI 1.130-1.667, p= 0.0014) in the total subjects. Even in the subjects without the drug therapy, the increased IDL-C as well as BMI were significant predictors for 10-year CHD risk> 10% of S-score as well as F-score. Conclusion: These results suggest the significant relevance of the increased IDL-C for CHD risk scores in middle-aged men free of CHD and stroke. Further investigations are needed in women and elderly subjects.